Guidance to Employers on Integrating E-Cigarettes/Electronic Nicotine Delivery Systems Into Tobacco Worksite Policy. Issue 3 (March 2015) - Whitsel, Laurie P.; Benowitz, Neal; Bhatnagar, Aruni; Bullen, Chris; Goldstein, Fred; Matthias-Gray, Lena; Grossmeier, Jessica; Harris, John; Isaac, Fikry; Loeppke, Ron; Manley, Marc; Moseley, Karen; et al.
Abstract : In recent years, new products have entered the marketplace that complicate decisions about tobacco control policies and prevention in the workplace. These products, called electronic cigarettes (e-cigarettes) or electronic nicotine delivery systems, most often deliver nicotine as an aerosol for inhalation, without combustion of tobacco. This new mode of nicotine delivery raises several questions about the safety of the product for the user, the effects of secondhand exposure, how the public use of these products should be handled within tobacco-free and smoke-free air policies, and how their use affects tobacco cessation programs, wellness incentives, and other initiatives to prevent and control tobacco use. In this article, we provide a background on e-cigarettes and then outline key policy recommendations for employers on how the use of these new devices should be managed within worksite tobacco prevention programs and control policies.